2014
DOI: 10.2174/1874325001408010423
|View full text |Cite
|
Sign up to set email alerts
|

Flap Decisions and Options in Soft Tissue Coverage of the Lower Limb

Abstract: The lower extremities of the human body are more commonly known as the human legs, incorporating: the foot, the lower or anatomical leg, the thigh and the hip or gluteal region.The human lower limb plays a simpler role than that of the upper limb. Whereas the arm allows interaction of the surrounding environment, the legs’ primary goals are support and to allow upright ambulation. Essentially, this means that reconstruction of the leg is less complex than that required in restoring functionality of the upper l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 95 publications
2
33
0
1
Order By: Relevance
“…These conditions include severe infection and local vascular problems. In the presence of infection the chance for success of plastic surgery is limited and additional surgery may be required to control infection prior to the major plastic surgery[5,14,15]. After severe trauma some limbs may be left with only one blood vessel and if it is used as a feeding artery for the graft this may threaten the limb life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions include severe infection and local vascular problems. In the presence of infection the chance for success of plastic surgery is limited and additional surgery may be required to control infection prior to the major plastic surgery[5,14,15]. After severe trauma some limbs may be left with only one blood vessel and if it is used as a feeding artery for the graft this may threaten the limb life.…”
Section: Discussionmentioning
confidence: 99%
“…This could be done by major plastic surgery in the form of local myocutaneous flaps, or free flaps. But, in the presence of infection the chance for success of these plastic surgeries becomes very limited[5,6]. During distraction osteogenesis all the tissues are lengthened including the bone, vessels, nerves, muscles and skin.…”
Section: Introductionmentioning
confidence: 99%
“…However, the problem with these island flaps is that they may offer solutions regarding vascularity, but when it comes to wound tension or handling load, they are inadequate --especially when larger skin lesions have been removed. Random cutaneous flaps have fared poorly on the lower limb and probably because most flaps have been raised superficial to the deep fascia [144] . Haertsch conducted a dyeinjection study on 22 post-mortem legs that demonstrated the role of the fascial plexus and his studies showed that skin flaps in the leg can only perform reliably if the deep fascia of the leg is included --confiring that for practical purposes, the "surgical plane" of the leg is deep to the deep fascia [145] .…”
Section: Special Situations: Scalp and Lower Limbmentioning
confidence: 99%
“…9). The principles of three-dimensional vascular anatomy revealed by their meticulous studies determine the choice of appropriate perforator flap, whether musculocutaneous (indirect) or septocutaneous (direct), used to reconstruct soft tissue defects (see Inoue & Taylor, 1996;Houseman et al 2000;Taylor et al 2011Taylor et al , 2012Griffin et al 2014;Jordan et al 2014).…”
Section: Angiosome Conceptmentioning
confidence: 99%